Vyatka Church Seals of Synodal Period: an Attempt at Classification (Collection of Sphragistics at P.V. Alabin Kirov Regional Local Lore Museum) - E. Yu. Mokerova; K. N. Tarasov (Научный диалог, 2023)
This article proposes a classification of Vyatka church seals from the 18th to the early 20th century based on materials from the collection of sphragistics at the P. V. Alabin Kirov Regional Local Lore Museum. The criteria for classification include the affiliation of the seals with specific individuals and institutions, as well as the specific images depicted on the seals. The article identifies four groups of seals: seals of church administration, seals of spiritual educational institutions, seals of churches, and personal seals of clergy. The study reveals that state symbols, such as the doubleheaded eagle, were typically depicted on seals of church administration and spiritual educational institutions. Seals of parish churches depicted real church buildings or saints until the first third of the 19th century when they were replaced by a standardized image of a three-domed church. Seals belonging to Vyatka bishops were typically twosided with images of a blessing hand and the Holy Trinity. From the mid-19th century, they were replaced by one-sided seals with images of two blessing hands. All personal seals of bishops have circular legends with their names. Seals belonging to other clergy members contain information about the owner’s name, initials, surname, and sometimes their rank. The most popular symbol for all groups of seals was the All-Seeing Eye, symbolizing God’s omniscience.